Perdegimo sindromo veiksniai gydytojo odontologo padėjėjo profesinėje aplinkoje - Rudėnienė, Virgina; Čepurnaitė, Sandra (Slauga. Mokslas ir praktika, 2023)
Burnout syndrome is a global problem among medical care specialists [1], the definitions of the concept of burnout syndrome are quite diverse, but the version of C. Maslach and S. Jackson is often used: "Burnout syndrome is a syndrome of emotional exhaustion, depersonalization and self-realization that can be experienced by working people [2].Research aim – to analyze the factors of burnout syndrome in the professional environment of the dental assistant.Research methods: analysis of scientific information sources, quantitative research: anonymous questionnaire survey.Most important results and conclusions. According to the study results, the main factors of inefficient work organization that contribute to the emergence of burnout syndrome are: high workload, insufficient salary, institution focusing to the quantity over quality and excessive assigned tasks per single dental assistant. The most significant factors, related to working conditions and microclimate are: constant pressure to perform assigned tasks as quickly as possible, lack of relatively calm and safe environment and inequality between the staff members. After evaluating the methods of burnout syndrome, the most effective individual ways of management were indicated: spending time with a family members, participating in activities, sports, yoga or meditation, also traveling and spending time in the nature, countryside or by the sea. The respondents highlighted the importance of burnout syndrome management by the institutional level, which includes the improvement of psychological climate in the working area, mutual support amongst the colleagues, also to maintain a calm and safe environment and ensure the personal space of employee by providing relaxation rooms in the facility.
Keywords: perdegimo sindromas; gydytojo odontologo padėjėjas; profesinė aplinka